2022
DOI: 10.1155/2022/1474273
|View full text |Cite
|
Sign up to set email alerts
|

miR-100-5p Promotes Epidermal Stem Cell Proliferation through Targeting MTMR3 to Activate PIP3/AKT and ERK Signaling Pathways

Abstract: Skin epidermal stem cells (EpSCs) play a critical role in wound healing and are ideal seed cells for skin tissue engineering. Exosomes from human adipose-derived stem cells (ADSC-Exos) promote human EpSC proliferation, but the underlying mechanism remains unclear. Here, we investigated the effect of miR-100-5p, one of the most abundant miRNAs in ADSC-Exos, on the proliferation of human EpSCs and explored the mechanisms involved. MTT and BrdU incorporation assays showed that miR-100-5p mimic transfection promot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“…Leptin induces proliferation and (or) anti-apoptosis effect of breast cancer cells and vascular smooth muscle cells by activating the PI3K pathway [44,45]. The ERK1/2 pathway has also been shown to play an important role in regulating the proliferation of a variety of stem cells [46][47][48]. In this study, it was found that leptin-induced NSCs proliferation was accompanied by an increase in phosphorylation of AKT and ERK1/2.…”
Section: Discussionmentioning
confidence: 54%
“…Leptin induces proliferation and (or) anti-apoptosis effect of breast cancer cells and vascular smooth muscle cells by activating the PI3K pathway [44,45]. The ERK1/2 pathway has also been shown to play an important role in regulating the proliferation of a variety of stem cells [46][47][48]. In this study, it was found that leptin-induced NSCs proliferation was accompanied by an increase in phosphorylation of AKT and ERK1/2.…”
Section: Discussionmentioning
confidence: 54%
“…The paracrine effects of EVs on cells regulate a broad range of functions, and they occur through the transportation of genetic materials, including mRNAs and miRNAs [ 25 ]. Three types of miRNAs, such as let-7b-5p, miR-23a-3p, and miR-100-5p, have been demonstrated to control regeneration-related processes, including angiogenesis, cell proliferation, migration, and others [ 26 , 27 , 28 ], and exert superior regeneration effects on the kidney [ 17 ], bone [ 29 ], and cartilage [ 30 ], respectively. We selected these miRNAs as some of the representative miRNAs used for regenerations, and quantitatively compared the expression levels of them in STV EVs, STV mEVs, CDM EVs, and CDM mEVs.…”
Section: Resultsmentioning
confidence: 99%
“…EpSCs were isolated from the skin of newborn mice as previously described [13, 14]. Briefly, skin tissues were collected from anesthetized mice, cut into 1.0×1.0 cm 2 pieces, and incubated in Dispase II (0.25%, Sigma, St Louis, USA) for 16-18 h at 4[.…”
Section: Methodsmentioning
confidence: 99%
“…MTT and BrdU incorporation assays were performed to measure the proliferation of EpSCs as previously described [13,14]. Optical density values were measured at 490 nm for MTT assay and at 450 nm for BrdU incorporation assay, using the Multiskan TM Spectrum Microplate Reader (Thermo Fisher, Massachusetts, USA).…”
Section: Cell Proliferation Assaysmentioning
confidence: 99%